Penerapan Model Pembelajaran Tematik dengan Pendekatan Make- A Match untuk Meningkatkan Hasil Belajar Siswa - Fuad, Choirul; Maghribi, Hamdan (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2024)
The SD/MI student learning process differs from that of the senior high school student. To ensure the success of SD/MI students, it is necessary to carefully consider all available study areas; nevertheless, each area of study must be closely related to the others. This study aims to analyze student learning outcomes after applying the Make A Match method. The research methodology used in this study is a combination of qualitative research methods and the Tindakan Kelas (PTK) method of research. This PTK is conducted in two sessions, with each session lasting two days. The subject of this research is 29 students from MIN 3 Klaten's VI grade. The instruments that are used include documentation, observation, and wawancara. Evaluation using process and result tables. The results of this study can improve the learning outcomes for students in Grade VI, MIN 3